DYNAMIC RENAL SCINTIGRAPHY POTENTIAL TO DIAGNOSE RENAL POSTTRANSPLANT COMPLICATIONS IN KIDNEY RECIPIENTS - A.V. Kapishnikov; A.V. Kolsanov; Yu.S. Pyshkina (Вестник трансплантологии и искусственных органов, 2014)
Aim of our clinical study was evaluation of the possibility of diagnosing of renal posttransplant complications in recipients using dynamic renal scintigraphy.Materials and methods. In this study were included 118 patients (age 21–60 (38,4 ± 9,8 yrs)), who underwent dynamic renal scintigraphy and renal transplantat biopsy. We determined time to peak uptake and excretion half-life time of radiopharmaceutical in renal transplantat and graft parenchyma. Recipients were subdivided into three groups according to histopathological findings: first – normal (n = 32), second – acute rejection (n = 43), third – chronic nephropathy (n = 43).Results. Time to peak uptake of radiopharmaceutical in graft parenchyma in patients in the fi rst group – 3,24 ± 0,54 min, second – 6,61 ± 3,28 min, third – 6,21 ± 3,17 min (p < 0,001). Time to peak uptake of radiopharmaceutical in renal graft in patients in the fi rst group – 3,87 ± 0,62 min, second – 7,4 ± 3,8 min, third – 8,03 ± 3,28 min (p < 0,001). The half-life time of radiopharmaceutical in graft parenchyma – 10,4 ± 2,95 min, second – 37,09 ± 19,44 min, third – 29,6 ± 15,52 min (p < 0,01). The half-life time of radiopharmaceutical in renal graft in the fi rst group – 12,31 ± 3,09 min, second – 43,29 ± 27,39 min, third – 52,71 ± 26,2 min (p < 0,001). Anderson–Bahadur distance: Tmax of graft parenchyma is the most signifi cant between the fi rst and the second group of patients (1,23); Tmax of renal graft gives maximum index value in chronic nephropathy (0,89), T1/2 of graft parenchyma is more once differentiated between acute rejection and chronic nephropathy (0,95). The sensitivity and the specifi city of renal scintigraphy parameters in the diagnosis of renal posttransplant complications amounted to 71,43–95,24% and 67,7–96,43%, respectively.Conclusion. Renal scintigraphy is an additional test for early detection of renal posttransplant complications and correction of recipient surveillance. The kinetic parameters of renotrophic radiopharmaceuticals provide diagnosis of acute rejection and chronic nephropathy of renal graft. The introduction of radionuclide imaging to monitor the state of renal transplantat optimizes approaches to graft biopsy.